Od wywiadu do rozmowy potocznej — o gatunkowych modyfikacjach medialnych rozmów ze sportowcami - Kacperska, Beata (Acta Universitatis Lodziensis. Folia Linguistica, 2018)
The aim of the paper is to characterize media genres which based on a dialogue between a journalist and a sportsman and to present their specific implementations on the example of conversations with volleyball players. The analysis uses the methodology of Maria Wojtak’s linguistic genology. On the basis of 65 verbal exchanges with sportsmen the author distinguishes the most important features of the contemporary media conversation. She takes into account its subject, structure, style of interlocutors’s expressions, functionality etc. The author presents the various forms of dialogue, through the description of the classical interactions (press, radio and internet interview), the conversations typical for sports journalism (micro-interview post-match) and the latest forms of communication with players (interview based on questionnaire in the form of video, conversation in the talk show, colloquial talk).